2020
DOI: 10.1111/dth.13309
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of noncultured melanocyte‐keratinocyte cell suspension vs hair follicular cell suspension transfer in stable vitiligo: A randomized controlled trial

Abstract: Noncultured melanocyte-keratinocyte cell transplantation (NMKT) and noncultured autologous hair follicular extracted cell suspension (HFECS) are surgical methods for stable vitiligo. 1 Our study aimed to compare NMKT with HFECS in stable vitiligo, in a randomized controlled study. Fifteen eligible patients older than 12 years were recruited. Patients were randomized for treatment with NMKT, HFECS, or placebo. The majority of lesions (66.7%) were on face and hands. The mean duration of disease was 14.17 ± 8.3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…While, Hamza et al reported higher re‐pigmentation with HFCS after 3 months, Moosavi et al noted good re‐pigmentation with ECS at the end of 4 months 9,11 . Both studies used NBUVB treatment post‐surgery and found no significant difference between the two methods 9,11 . In the present study, percentage re‐pigmentation with both ECS and HFCS improved over time, with the former being significantly superior at weeks 4 and 16.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…While, Hamza et al reported higher re‐pigmentation with HFCS after 3 months, Moosavi et al noted good re‐pigmentation with ECS at the end of 4 months 9,11 . Both studies used NBUVB treatment post‐surgery and found no significant difference between the two methods 9,11 . In the present study, percentage re‐pigmentation with both ECS and HFCS improved over time, with the former being significantly superior at weeks 4 and 16.…”
Section: Discussionsupporting
confidence: 39%
“…Donaparthi et al observed that 83.3% and 43.3% of the total 11 participants in their study exhibited an excellent re‐pigmentation with ECS and HFCS, 6 months post‐surgery, respectively with ECS being significantly superior 10 . While, Hamza et al reported higher re‐pigmentation with HFCS after 3 months, Moosavi et al noted good re‐pigmentation with ECS at the end of 4 months 9,11 . Both studies used NBUVB treatment post‐surgery and found no significant difference between the two methods 9,11 .…”
Section: Discussionmentioning
confidence: 98%